2020
DOI: 10.1371/journal.pone.0230023
|View full text |Cite
|
Sign up to set email alerts
|

Detection of melon necrotic spot virus by one-step reverse transcription loop-mediated isothermal amplification assay

Abstract: Melon necrotic spot virus (MNSV) can cause significant economic losses due to decreased quality in cucurbit crops. The current study is the first to use reverse transcription loop-mediated isothermal amplification (RT-LAMP) for detection of MNSV. A set of four LAMP primers was designed based on the coat protein gene sequence of MNSV, and a RT-LAMP reaction was successfully performed for 1 h at 62˚C. The results of RT-LAMP showed high specificity for MNSV and no cross-reaction with other viruses. Compared to tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Similarly, Melon necrotic spot virus (MNSV) has been diagnosed for the first time which causes significant economic losses in cucurbit crops using RT-LAMP. In their study, authors reported high specificity of RT-LAMP for MNSV without any cross-reaction with other viruses [ 115 ]. Eventually, different versions of LAMP are being developed for its more feasible use.…”
Section: Methods For Plant Viral Diagnosticmentioning
confidence: 99%
“…Similarly, Melon necrotic spot virus (MNSV) has been diagnosed for the first time which causes significant economic losses in cucurbit crops using RT-LAMP. In their study, authors reported high specificity of RT-LAMP for MNSV without any cross-reaction with other viruses [ 115 ]. Eventually, different versions of LAMP are being developed for its more feasible use.…”
Section: Methods For Plant Viral Diagnosticmentioning
confidence: 99%
“…Colorimetric 74 Xanthomonas albilineans 100 fM DNA Sugarcane xylem sap Colorimetric 75 Rhizoctonia solani 1.65 fg ml −1 of template DNA Leaves Colorimetric 76 Sarocladium oryzae 1.6 fg ml −1 of the template DNA Soil and weeds Colorimetric 77 Phoma macdonaldii 10 conidia per g Leaves, stems, and seeds Colorimetric 71 Colletotrichum gloeosporioides 10 nM RNA Mycelium Colorimetric 78 Melon necrotic spot virus 7.5 × 10 −3 mg mL −1 of total RNA Melon leaves…”
Section: Leavesmentioning
confidence: 99%